Implementasi Teori Hirarki Kebutuhan Abraham Maslow terhadap Peningkatan Kinerja Pustakawan - Iskandar, Iskandar (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
One should concern in how to keep an organization keeps balanced is depending on its human resources. Humanbeings can make an organization effectively works, and might design all operational works, till to produce value things, to control its quality measurments, to promote, in which above all is to achiece the organization goals. Having such a quality person within an organization might lead to success. The current study investigates Maslow’s hierarchy of needs theory and McClelland’s human motivation theroy that being used in many organization around the globe, including library. The study is a library research in which it will discover the impact of the theories within library as an information institution that worked human resources to establish.